PHYSICAL EDUCATION AS A MANDATORY PART OF THE EDUCATIONAL PROCESS IN HIGHER EDUCATIONAL INSTITUTIONS - Antipova, Zhanna; Barsukova, Tatyana (Sworld-Us Conference proceedings, 2025)
The work analyzes the importance and problems of physical education in legal institutions of higher education. It is emphasized that physical education of students plays a key role in ensuring the harmonious development of the personality and training of